Identification of Water Biota in the Mangrove Forest Water Area in Aek Horsik Village, Tapanuli Tengah District - Batubara, Lenni Wahyuni; Santikawati, Susi; Siburian, Sar Aloha Martupa (Journal of Coastal and Ocean Sciences, 2024)
Mangrove forests are a typical ecosystem in coastal areas that accommodate a variety of species, are breeding grounds for marine biota, and have economic value in improving community welfare. Based on the search data results, various aquatic organisms, such as Mollusca, Crustacea, and fish, use mangroves as a nursery, shelter, and breeding habitat. This research aims to identify the diversity of aquatic biota in the mangrove forest waters in Aek Horsik Village, Tapanuli Tengah Regency and was carried out from May to June 2023. This research used a survey method with a purposive sampling technique, analyzed descriptively with abundance formulas and dominance indices. The research station is divided into three stations. Station 1 is located in the upstream mangrove forest waters, station 2 is located in the middle of the mangrove forest waters, and station 3 is located downstream of the mangrove forest waters. Based on the results of research in the waters of the Aek Horsik mangrove forest, it was found that there were ten types of macrozoobenthic biota consisting of the Gastropoda class inhabited by six families, the Bivalvia class inhabited by two families and the Crustacea class inhabited by 2 Portunidae families with an abundance of 10,648 individuals and the fish biota of 8 species consisting of 8 families with abundance numbering 111 ind